Effect of being active in participating in group guidance services on the independence of students - Esti Wulandari; Suhertina Suhertina; Herman Nirwana (Indonesian Institute for Counseling, Education and Theraphy, 2020)
This research is motivated by the fact that group counseling services are conducted well, but the independence of students is still low. This study aims to determine 1) how high the activity of joining a group counseling service 2) the independence of student students 3) the significant effect of the activity of joining a group counseling service on the independence of KTP students. This research is correlational. The subjects of this study were all students consisting of 156 students and the object was the effect of the activity of joining a group counseling service on student independence. 61 students were sampled from this study. These findings reveal that the activeness of students to join group counseling services in the KTP Department is very high (86.85%). The independence of students in the Department of KTP is high (75.61%). There is a significant influence of the activity of joining a group counseling service on the independence of students in the KTP Department with 0.545 at a probability level of 0,000. It was obtained from robserved which was higher than rtable at significant levels of 5% and 1% (0,250 <0.545> 0.325). The percentage of the effect of the activity of joining a group counseling service on student independence is 29.7% and the remaining 70.3% is influenced by other variables not mentioned in this study.